PENGEMBANGAN LEARNING MANAGEMENT SYSTEM AL TALKHĪS LI AL- ISTIMᾹ’ (ATLIS) - Faliqul Isbah (STIQ Amuntai, 2023)
The creativity of educators in managing and developing learning media is improving, especially during the pandemic, where the necessity of online learning must be carried out. Even as the pandemic is gradually being controlled, learning media development continues. For instance, developing the Learning Management System (LMS) for listening skills in Arabic language learning, particularly Maharah Istima', is a crucial and fundamental language acquisition skill. This research aims to determine suitable criteria for Istima' learning media and the development of the LMS At-Talkhis Li Al-Istima'. This research utilizes the Research and Development approach, employing the Waterfall model consisting of the following stages: analysis, design, implementation, testing, and maintenance. In the analysis stage, a series of analyses is conducted regarding the criteria used for Istima' learning. Subsequently, the design of the LMS AT-Talkhis Li Al-Istima' is developed, followed by the utilization of the media and feasibility testing carried out by media experts, subject matter experts, and students. The results of this research are the criteria for determining Istima' learning media, considering the curriculum, media, and content aspects. Meanwhile, the LMS AT-Talkhis Li Al-Istima' is a portable document file (PDF) that is integrated with links to relevant media, materials, assignments, or websites. The feasibility of the LMS At-Talkhis Li Al-Istima', both in terms of media quality and usability, meets the criteria for being good.